2017
DOI: 10.1002/anie.201706703
|View full text |Cite
|
Sign up to set email alerts
|

Polyproline as a Minimal Antifreeze Protein Mimic That Enhances the Cryopreservation of Cell Monolayers

Abstract: Tissue engineering, gene therapy, drug screening, and emerging regenerative medicine therapies are fundamentally reliant on high‐quality adherent cell culture, but current methods to cryopreserve cells in this format can give low cell yields and require large volumes of solvent “antifreezes”. Herein, we report polyproline as a minimum (bio)synthetic mimic of antifreeze proteins that is accessible by solution, solid‐phase, and recombinant methods. We demonstrate that polyproline has ice recrystallisation inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
116
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 41 publications
(47 reference statements)
2
116
0
2
Order By: Relevance
“… 6 , 7 Gibson and co-workers have developed synthetic polymers 8 , 9 based upon poly(vinyl alcohol) and poly(ampholytes) which have been found to enhance the cryopreservation of blood 10 12 and nucleated cells. 4 , 13 …”
mentioning
confidence: 99%
“… 6 , 7 Gibson and co-workers have developed synthetic polymers 8 , 9 based upon poly(vinyl alcohol) and poly(ampholytes) which have been found to enhance the cryopreservation of blood 10 12 and nucleated cells. 4 , 13 …”
mentioning
confidence: 99%
“…Indeed, study of various length polyproline showed that it has ice recrystallization inhibition activity owing to its amphipathic PPII helix structure. 33 Therefore, the identification of PPII extended helical conformations for LEA and other similar peptides and proteins that exist in low hydration, high salinity, or extreme temperatures suggests the structure assists in damage prevention during desiccation, ionic and osmotic stress, and freezing by retaining water molecules. [34][35][36][37][38][39][40] For example, Soulages et al previously reported recombinant Group 1 LEA (GmD-19) and Group 2 LEA (GmDHN1) proteins from soybean existing in the extended PPII helical conformation in aqueous conditions and low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, synthetic macromolecular mimics of AFPs have emerged, which can reproduce their properties but benefit from the scalable and tunable synthesis of synthetic polymers. 18,21,22 These have been used to enhance the cryopreservation of mammalian cells including blood, 2325 cell lines, 26 and primary cells. 27,28 Their primary function is ice recrystallization inhibition, where the rate of growth (not formation) of ice is slowed, leading to reduced cell death during thawing.…”
Section: Introductionmentioning
confidence: 99%